On the Tensile Tests of Polyurethane and Its Composites with Carbon Nanotubes - Martin Kuběna; Marek Eliáš; Lenka Zajíčková; Jan Poduška; Tomáš Kruml (Advances in Materials Science and Engineering)
Neat polyurethane (PU) specimens and composites of polyurethane with variable amounts of multiwalled carbon nanotubes (MWCNTs) were subjected to tensile tests, stress relaxation tests, and strain rate jumps. Since the already published data about the effect of carbon nanotubes addition to polymer matrix are somewhat contradictory, great care was taken to understand the mechanical properties of neat PU specimens. The studies revealed that the tensile curves of neat PU are substantially influenced by several factors, such as strain rate, age, and thickness of the specimens. The addition of MWCNTs into the PU matrix had a negligible effect on the mechanical properties of composites at low strains (ε < 0.2). With increasing strain, the MWCNTs addition augmented the strength of the composites, and at high local deformations, as in the previously reported indentation experiments, the adhesion strength between functionalized carbon nanotubes and PU matrix substantially influences the mechanical behavior. The material response to the transient mechanical test showed an Arrhenius-type behavior and was analyzed accordingly. The magnitude of the activation volume scaled with the average length of the free segment of the polymer molecules.